Vacuum assisted closure therapy in children with complicated abdominal wounds, with or without viscero-cutaneous fistulae - Mostafa M. Elghandour; Osama El Naggar; Ahmed Bassiouny Radwan; Mohammed Abdel-Latif (Elsevier, 2024)
Background: Management of complicated abdominal wounds is challenging in children. Vacuum-assisted closure proved to be beneficial. We aimed to report the outcome of VAC over 5 years' practice in complicated abdominal wounds with or without viscero-cutaneous fistulae. Methods: Retrospective review of children managed by VAC over 5 years, from January 2017 to December 2022. Included patients had complicated abdominal wounds. Customized VAC devices with continuous negative pressure were used for all patients. The applied pressure was tailored according to the patient's age and the wound condition. Results: Nineteen patients were included, their ages ranged from 3 months to 15 years. Peritonitis was the main pathology in 12 patients, abdominal wall infection in 4, and a combination of both in 3. VAC was applied over closed wounds in 10 patients and over open wounds in 9; 6 of them had cutaneous fistulae. The median duration of VAC application over closed wounds was 7.5 days, while it was 10 days in open wounds. VAC promoted healing in closed and narrow-gapped wounds, while it was successfully used as a bridging therapy in 4 patients with wide-gapped wounds. Patients with viscero-cutaneous fistulae were successfully managed without further surgical intervention. VAC was complicated by fascial dehiscence with evisceration and incisional hernia in two patients. Conclusion: VAC could be beneficial to complicated abdominal wounds in pediatric age. It was helpful in managing small viscero-cutaneous fistulae.